A functional “metacarpal-hand” after a firework injury obtained without any flap or toe-transfer. - D'Orio, Marco; Taccardo, Giuseppe; Passiatore, Marco; Macrì, Giulia; Starnoni, Marta; De Vitis, Rocco (Acta Biomedica Atenei Parmensis, 2023)
A 37-year old male patient with a right-hand firework injury. An extreme hand reconstruction was performed. The second and third rays were sacrificed enlarging the first space. The diaphysis of the second metacarpal bone became a tubular graft to reconstruct the fourth metacarpal. The thumb consisted only in the first metacarpal bone. The result was satisfactory, according to the wishes and needs of the patient, a three-finger hand with an opposable thumb, obtained in only one surgical treatment and without using free flaps. The concept of an “acceptable hand” is related to the surgeon’s and patient’s opinions.